Ginsenoside Rb1 and Rd Remarkably Inhibited the Hepatic Uptake of Ophiopogonin D in Shenmai Injection Mediated by OATPs/oatps - Liu, Xiaopei; Chen, Lin; Liu, Mingyi; Zhang, Hong; Huang, Shibo; Xiong, Yuqing; Xia, Chunhua (Frontiers in Pharmacology, 2018)
Shenmai injection (SMI) is derived from traditional Chinese herbal prescription Shendong yin and widely used for treating cardiovascular diseases. Ophiopogonin D (OPD) is one of the main active components of SMI. The hepatic uptake of OPD is mediated by organic anion-transporting polypeptides (OATPs/oatps) and inhibited by some other components in SMI. This study aimed to identify the active components of SMI responsible for the inhibitory effects on hepatic uptake of OPD in rats and explore the compatibility mechanisms of complex components in SMI based on OATPs/oatps. The known effective fractions, the known components in Shenmai Formula, and the fractions obtained from SMI by HPLC gradual-separation technology were individually/combinedly tested for their effects on OPD uptake in rat primary hepatocytes and recombinant OATP1B1/OATP1B3-expressing HEK293T cells. The results indicated that the OPD uptake was inhibited by panaxadiol-type ginsenosides (ginsenoside Rb1 and Rd), but slightly influenced by panaxatriol-type ginsenosides in rat primary hepatocytes and recombinant cells. The fractions of SMI-3-1 (0-11 min) and SMI-3-3 (15-20 min) obtained by HPLC gradual-separation technology were proved to be the major effective fractions that influenced the OPD uptake, and subsequently identified as ginsenoside Rb1 and Rd, respectively. The plasma concentrations of OPD in rats given OPD+ginsenoside Rb1+ginsenoside Rd were higher compared to rats given OPD alone at the same dose. In conclusion, ginsenoside Rb1 and Rd are the major effective components in SMI that remarkably inhibited the hepatic OPD uptake mediated by OATPs/oatps. The interaction of complex components by OATPs/oatps may be one of the important compatibility mechanisms in SMI.